Distributions, Sources, and Backward Trajectories of Atmospheric Polycyclic Aromatic Hydrocarbons at Lake Small Baiyangdian, Northern China - Ning Qin; Xiang-Zhen Kong; Ying Zhu; Wei He; Qi-Shuang He; Bin Yang; Hui-Ling Ou-Yang; Wen-Xiu Liu; Qing-Mei Wang; Fu-Liu Xu (The Scientific World Journal)
Air samples were collected seasonally at Lake Small Baiyangdian, a shallow lake in northern China, between October 2007 and September 2008. Gas phase, particulate phase and dust fall concentrations of polycyclic aromatic hydrocarbons (PAHs) were measured using a gas chromatograph-mass spectrometer (GC-MS). The distribution and partitioning of atmospheric PAHs were studied, and the major sources were identified; the backward trajectories of air masses starting from the center of Lake Small Baiyangdian were calculated for the entire year. The following results were obtained: (1) The total concentration of 16 priority controlled PAHs (PAH16) in the gas phase was 417.2±299.8 ng·m−3, in the particulate phase was 150.9±99.2 ng·m−3, and in dust fall was 6930.2±3206.5 ng·g−1. (2) Vehicle emission, coal combustion, and biomass combustion were the major sources in the Small Baiyangdian atmosphere and accounted for 28.9%, 45.1% and 26.0% of the total PAHs, respectively. (3) Winter was dominated by relatively greater PAHs polluted northwesterly air mass pathways. Summer showed a dominant relatively clean southern pathway, whereas the trajectories in autumn and spring might be associated with high pollution from Shanxi or Henan province.